Decline in HPV-vaccination uptake in Denmark – the association between HPV-related media coverage and HPV-vaccination - Camilla Hiul Suppli; Niels Dalum Hansen; Mette Rasmussen; Palle Valentiner-Branth; Tyra Grove Krause; Kåre Mølbak (BMC Public Health, 2018)
Abstract Background In 2014, Denmark experienced a rapid decline in vaccination uptake for the human papillomavirus (HPV) vaccine after a successful introduction of the vaccine in 2009. Before the decline, the uptake of the first HPV vaccine was around 90% for girls born in the period 1998 to 2000, while it dropped to 54% for girls born in 2003. The decline followed negative public attention from 2013 coinciding with increasing suspected adverse-event reporting to the Danish Medicines Agency. The aim of this study is to describe the HPV-vaccination uptake, to quantify relevant HPV-related media coverage, and analyse the relation between media coverage and HPV-vaccination acceptance in Denmark in year 2009–2016. Methods Three types of data were used for the analysis: Immunisation data from 243,415 girls, media coverage (8524 news items) and Google search activity. We used changes in the correlation between media coverage and vaccination uptake to identify a changing point in their relationship. The relationship before and after the changing point was analysed determined on the interactions between vaccination uptake, media and search activity, with search activity as a proxy for public attention. Results We identified July 2013 as a changing point in the relationship between media coverage and vaccination uptake. We found no significant relationship between media coverage and vaccination uptake in the first part of the time series (June 2009 to June 2013), whereas from July 2013 and onwards there was a negative Pearson’s correlation of − 0.52. The changing point coincides with both an increase in Google searches for “HPV side effects” and media coverage with negative content. Conclusions Following a successful launch of the HPV-vaccination programme, concerns about vaccine safety shifted the public opinion and the coverage by the media. The noticeable shift in correlation between vaccination uptake and media coverage before and after July 2013 could indicate that increased media coverage influenced the decline in vaccination uptake. Media monitoring may represent an important tool in future monitoring and assessment of confidence in vaccination programmes.